Fenomena “The Nuruls” Di Kota Depok. (Studi Fenomenologi Remaja Berhijab Di Kota Depok) - Sartika, Novia Dwi; Erlangga, Christhoper Yudha (CV. ITTC INDONESIA, 2024)
This study examines the phenomenon of